Remediation of Heavy Metals in the Leachate of the Final Waste Processing Site Using Magnetite Nanoparticles - Iswandi Iswandi; Dwi Puryanti; Elvaswer Elvaswer (Green Publisher Indonesia, 2022)
Nanoparticles are iron oxides that are used in various fields of life, one of which is to absorb heavy metals. In this study, magnetite (Fe3O4) nanoparticles were synthesized using the correspirate method and magnetite nanoparticle templates with PEG-6000. Synthesis of magnetite nanoparticles was carried out to obtain magnetite nanoparticles to be used to remediate heavy metals Cu, Ni and Mn in waste leachate. The susceptibility analysis of the leachate sample type showed that the type of magnetic material. The calculation results from the XRD diffractogram obtained that the crystal size of Fe3O4 nanoparticles is 56.35 nm. By varying the mass of 0.4 grams of Fe3O4, 0.8 grams of Fe3O4 and coating Fe3O4 using PEG 6000, it is known that the reduction in the concentration of heavy metal Cu is 7.71%, 23.09% and 42.31%, respectively. The percentage reduction in the concentration of heavy metal Ni was 6.29%, 9.45% and 7.09%, respectively.The percentage reduction in the concentration of heavy metal Mn was 25.369%, 19.98% and 4.05%, respectively. This indicates that Fe3O4 and PEG-6000 nanoparticles are able to reduce the concentration of heavy metals in waste leachate contained in the leachate sample